2019
DOI: 10.2174/1874210601913010410
|View full text |Cite
|
Sign up to set email alerts
|

How to Sterilize 3D Printed Objects for Surgical Use? An Evaluation of the Volumetric Deformation of 3D-Printed Genioplasty Guide in PLA and PETG after Sterilization by Low-Temperature Hydrogen Peroxide Gas Plasma

Abstract: Introduction: In the present time, there is rapid development in the application of 3D printing technology in surgery. One of the challenges encountered by the surgeon is the sterilization of these 3D-printed objects for use in the operating room. Materials and Methods: Forty-two identical cutting guides used for genioplasty were 3D-printed: twenty-one in Polylactic acid (PLA) and twenty-one in Polyethylene terephthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 9 publications
2
49
0
1
Order By: Relevance
“…In order to use optimal parameter settings for segmentation procedure from CT scanning to virtual model reconstruction, in the present study, we used certi ed commercial software a that speci es accuracy is below scanning resolution and clinical relevance [29]. This means the bone models can be used for presurgical rehearsal and further clinically relevant applications in bone surgery [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…In order to use optimal parameter settings for segmentation procedure from CT scanning to virtual model reconstruction, in the present study, we used certi ed commercial software a that speci es accuracy is below scanning resolution and clinical relevance [29]. This means the bone models can be used for presurgical rehearsal and further clinically relevant applications in bone surgery [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…The sterilization methods adequate for different 3D-printing materials have been tested in terms of infection rate, mechanical performance, and dimensional stability, or, on the contrary, geometrical deformation (7,9,15,(19)(20)(21). Low-temperature hydrogen peroxide gas plasma has been an optimal sterilization procedure for printouts produced by FDP in ABS.…”
Section: Discussionmentioning
confidence: 99%
“…Visors can be manufactured from several types of materials that include polycarbonate, propionate, acetate, poly(vinylchloride), and PETG [9]. Since PLA and PETG are known to show volume change during sterilization processes [21], one-time use of the visor is recommended, whereas a study showed that sterilized 3-D printed surgical splints using filaments based on lignin (Green-TEC Pro) remained dimensionally stable [22]. The sterilization of the frame might be possible, but was not tested in this study.…”
Section: Materials Selectionmentioning
confidence: 99%